Optimization of Defective Coffee Beans Decaffeination Using Palm Oil - Dian Shofinita; Dianika Lestari; Sekar Ayu Ambarwati; Karen Christine Gunawan; Amarthya Benigna Achmadi (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
Defective coffee beans amount to 15-20% of the total produced coffee beans. The defective coffee bean contains caffeine, which can negatively affect the human body, such as increased heart rate, and thus sensitive to consumption by some people. This study aims to optimize the decaffeination process of defective coffee beans. The extraction of aroma and flavor compounds was done by maceration, and the decaffeination was carried out using palm oil as a solvent. The type of beans (green and roasted beans), the decaffeination contact time, and the ratio between coffee bean extract and solvent were varied in this study. The caffeine content was quantified, and the organoleptic and color tests were done on the concentrated coffee extracts. It was found that the higher the amount of solvent volume in decaffeination, the higher the caffeine decrease. In addition, the longer the green beans’ decaffeination time, the lower the caffeine decrease. Decaffeination using green coffee beans resulted in a greater reduction of caffeine (6.515-48.241%) than roasted coffee beans (8.495-24.272%). The optimum operating condition of green coffee bean decaffeination was the coffee bean extract and solvent ratio of 1:5.82 and the decaffeination time of 26.5 minutes. The organoleptic test result shows that decaffeinated coffee flavor had the same preferability as the commercial coffee flavor and was thus able to compete in the market.